2022
DOI: 10.3389/fimmu.2021.804416
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Immune Responses by Virus-Mimetic Polymeric Nanostructures Against Infectious Diseases

Abstract: Intermittent outbreaks of global pandemic disease have spurred new sensors and medicines development for the prevention of disease spread. This perspective specifically covers recent advances, challenges, and future directions in virus-mimetic polymeric nanostructures and their application in biological medicines with a special emphasis on subunit vaccine development. With tailorable compositions and properties, polymers facilitate the ingenious design of various polymeric nanostructures. As one type of polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…A few studies have reported that nanopillar structures or nanopatterned features could influence immune cells, especially DCs. [33][34][35][36][37][38] Co-stimulatory molecules (CD80 and CD86) expressions have been used to estimate the maturation level of DCs. Flow cytometry analysis in Figure 4a shows that pAu Pd HSs could increase the percentage of matured DCs by 20%, like the positive control (lipopolysaccharide [LPS]) of 20.9%, which is a powerful promoter of the maturation of DC.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have reported that nanopillar structures or nanopatterned features could influence immune cells, especially DCs. [33][34][35][36][37][38] Co-stimulatory molecules (CD80 and CD86) expressions have been used to estimate the maturation level of DCs. Flow cytometry analysis in Figure 4a shows that pAu Pd HSs could increase the percentage of matured DCs by 20%, like the positive control (lipopolysaccharide [LPS]) of 20.9%, which is a powerful promoter of the maturation of DC.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, POM surfaces are rich in oxygen, hydroxyl, and/or water ligands, suggesting that POM-based materials are excellent candidates for biomimetic applications. Over the last decades, POMs have demonstrated their promising biological activities, such as antitumoral ( Bijelic et al, 2019 ), antimicrobial ( Xu et al, 2020 ; Chen et al, 2021 ; Chen et al, 2022 ), insulin-sensitizing ( Chen et al, 2020 ), immune-enhancing activities ( Li et al, 2021 ; Li et al, 2022 ). In virtue of their structural diversity and physicochemical properties, POM-based nanomaterials exert oxidoreductase-mimicking activities, including oxidase, peroxidase ( Chen K. et al, 2018 ; Jia et al, 2019 ), and catalase ( Yadav and Singh, 2021 ).…”
Section: Introductionmentioning
confidence: 99%